Peningkatan Kapasitas Manajemen Keuangan dan Pemasaran Berbasis Digital Kelompok Usaha UJ.Mart Utami Jaya Grogol - Prihandoko, Prihandoko; Setyawati, Dyah Mieta; Prihantoro, Edy (Jurnal Media Pengabdian Komunikasi, 2024)
Abstract Utami Jaya's UJ Mart business group is located in Grogol Village, Limo District, Depok City, West Java Province. As a grocery store business group, the goods and services traded are retailers of basic food items, various snacks, packaged drinks, and cigarettes, providing Aqua Galon and 2.5kg Elpiji gas and grilled chicken food menus. The results of field findings show the advantages of the grocery store business as the target partner and a number of weaknesses of the target partner, which are presented as findings of partner problems. The priority problem of Partners is financial management and digital marketing, which is still done manually so that it is not in accordance with current conditions, where competitors of the same type have implemented modern retail businesses with business locations close to the location of Partners. The results of the activity show that the implementation of the use of technology and financial services, strengthening digital brands and online partnership strategies, is an investation and solution to the problems of target partners who have not adopted technology since their establishment in 2007. The results of this community service activity, greatly help the UJ.Mart Utami Jaya business group to increase shopping comfort and ease of making transactions as added value for customers, as well as create creative and modern shop signage, increasing the number of buyers who come to the location and increasing sales volume. Keywords: Increased capacitance; financial management; digital marketing; business group. Abstrak Kelompok usaha UJ. Mart Utami Jaya berlokasi di Kelurahan Grogol, Kecamatan Limo, Kota Depok, Provinsi Jawa Barat. Sebagai kelompok usaha toko kelontong, barang dan jasa yang diperdagangkan adalah pengecer barang sembako, aneka snack, minuman kemasan dan rokok, menyediakan Aqua Galon dan gas Elpiji 2.5kg serta menu makanan ayam bakar. Hasil temuan dilapangan menunjukkan keunggulan usaha toko kelontong sebagai Mitra sasaran serta sejumlah kelemahan Mitra sasaran yang disampaikan sebagai temuan permasalahan mitra. Permasalahan Prioritas Mitra adalah pengelolaan keuangan dan pemasaran digital yang masih dilakukan secara manual sehingga tidak sesuai dengan kondisi saat ini, dimana munculnya kompetitor sejenis yang telah menerapkan usaha retail modern dengan lokasi usaha yang berdekatan dengan lokasi Mitra. Hasil kegiatan menunjukkan bahwa implementasi pemanfaatan teknologi dan layanan keuangan, penguatan merek digital dan strategi kemitraan online merupakan investasi dan solusi permasalahan Mitra sasaran yang sejak berdirinya tahun 2007 belum melakukan adopsi teknologi. Hasil kegiatan Pengabdian kepada Masyarakat ini, sangat membantu kelompok usaha UJ.Mart Utami Jaya untuk meningkatkan kenyamanan belanja dan kemudahan melakukan transaksi sebagai nilai tambah bagi pelanggan, serta menciptakan papan nama toko yang kreatif dan modern, meningkatkan jumlah pembeli yang datang kelokasi dan peningkatan volume penjualan. Kata-kata kunci: Peningkatan Kapasitas; manajemen keuangan; pemasaran digital; kelompok usaha.